Economic and environmental aspects of Pokkali Rice- Prawn production system in central Kerala - P Ranjith, KR Karunakaran and C Sekhar (International Journal of Fisheries and Aquatic Studies, 2018)
Pokkali rice-prawn farming practice is a traditional rice-fish cultivation system found only in the coastal areas of Central Kerala where the height of water column of the field increases more than 100 CM during the South-West Monsoon. This system utilizes the symbolic relationship between rice and prawns. This is a natural system of cultivation which relies upon monsoons and sea tides. Rice residues form the feed for prawns and the excreta of Prawns formed the fertilizer for rice, which makes it ecologically stable and also reduces the input by maintaining a mutualistic approach. The study was conducted among Pokkali-Prawn, Non-Pokkali- Cowpea and Semi Intensive Prawn systems present in Ernakulum and Alappuzha Districts of Kerala. The net returns generated from these systems were estimated to be of Rs. 2.80 lakhs; Rs. 0.69 lakhs and Rs. 1.55 lakhs per ha with the Benefit Cost Ratio of 2.17, 1.45 and 1.31 respectively. Partial Budgeting exercise of sole Pokkali rice cultivation to Pokkali-Prawn Integrated system has resulted an income enhancement of Rs 3.75 lakhs and Partial Budgeting of Semi-Intensive Prawn cultivation to Pokkali-Prawn cultivation resulted an increase of income by Rs. 0.93 lakhs for every ha of cultivation. Such a profitable venture can be taken up scientifically without reducing the ecological health by an agripreneur.